The Importance and Evaluation of Environment-Friendly Megaprojects - As Perceived By Users - Csiszarik-Kocsir, Agnes; Varga, Janos (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
The environmental degradation of our time, the environmental devastation of previous years and global warming have presented the world with new and novel challenges that were not experienced in previous decades. Rising sea levels, increasing energy demand and the explosion in energy prices have created new focal points in the thinking of all spheres of economic life. The environmental degradation of fossil fuels has led to an increasing focus on renewable energy sources and innovative solutions. The aim of this paper is to examine the main issues outlined above through the examples of two flagship megaprojects. The study will examine the Maldivian floating city and the European Energy Island project from a user perspective, specifically in terms of their environmental and visionary messages. In this study, we will examine the two flagship projects through the results of a primary research, formulating the main messages for the design of the future projects. The aim of the study is to demonstrate the importance of environmental considerations in the definition of project scope, in order to give a starting point for projects with similar objectives, and to give ideas for their design and implementation. The acceptance of any project by its users is a key success factor, as the two projects under review are intended to demonstrate.